2017
DOI: 10.5301/ijao.5000633
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Regional Citrate Anticoagulation in Continuous Renal Replacement Therapy in Critically Ill Patients

Abstract: These results suggest that the implementation of CVVHDF with RCA using concentrated citrate solutions prolongs filter lifetime, achieves a longer effective hemodiafiltration time and is a safe and feasible method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
4
7
0
Order By: Relevance
“…The results of our present study suggested that RCA was more effective than LMWH in prolonging the filter lifespan in severe hypercalcemia patients who underwent CVVH. These results were consistent with previous studies of patients without hypercalcemia [23][24][25][26]. In the RCA group, the estimated median filter lifespan was >72 h, which was comparable with the filter lifespan in previous studies [18][19][20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our present study suggested that RCA was more effective than LMWH in prolonging the filter lifespan in severe hypercalcemia patients who underwent CVVH. These results were consistent with previous studies of patients without hypercalcemia [23][24][25][26]. In the RCA group, the estimated median filter lifespan was >72 h, which was comparable with the filter lifespan in previous studies [18][19][20].…”
Section: Discussionsupporting
confidence: 92%
“…The major intervention to maintain patency of the extracorporeal circuit is anticoagulation. Numerous clinical studies have demonstrated that regional citrate anticoagulation (RCA) for CRRT could prolong the filter lifespan and decrease the bleeding risk compared to heparin or low molecular weight heparin (LMWH) anticoagulation [23][24][25][26]. The Kidney Disease Improving Global Outcomes (KDIGO) guidelines recommended RCA as the first choice for CRRT in patients without citrate contraindications [15].…”
Section: Introductionmentioning
confidence: 99%
“…The present results compare well with similar studies, using this protocol in a general intensive care unit (ICU) population (27 h) and postoperative cardiac surgical patients who received RCA predilution continuous hemofiltration (48 h), continuous hemodiafiltration with RCA or heparin (50-58 h) and continuous hemodialysis with RCA (39-61 h) [10,[14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 85%
“…The observed longer filter life and lower rate of circuit clotting associated with RCA are largely consistent with previously reported data [5,[12][13][14][15][16]. In particular, it is similar to that observed in cohorts using a similar RCA protocol [11].…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
“…The reported incidence of metabolic complications associated with RCA is higher than previously reported [12,14,15]. This is possibly related to our decision to report any anomaly irrespective of its duration and poten-tial clinical significance.…”
Section: Comparison With Previous Studiesmentioning
confidence: 71%